Conflito ambiental no território Tapuya Kariri e suas implicações à saúde - Vasconcelos, Dayse Paixão e (2014)
The context of environmental conflict arises when there is a dispute attributed to the nature and territory, generating undesirable to one of the groups that live there. The research portrays the environmental conflict experienced by ethnic Tapuya Kariri, at Sierra Ibiapaba, and the health implications that it has provided. Its general objective was: To analyze the environmental conflict in the territory of indigenous Tapuya Kariri and its health implications, the indigenous perspective. The specific objectives were: to identify the concept of Health for the people Tapuya Kariri; Characterize the environmental conflict and its implications to the environment, labor and health; Identify the health needs arising from the context of environmental conflict; Identify the actions of health promotion that local UBS must perform in Indian perspective. The study took place in Gameleira village, located in the countryside of São Benedito, Ceará. It is a participant research, in which the study subjects were identified as research group. Seven meetings that constituted visits, meetings, village walks and thematic workshops were held. The analytical categories are described as follows: indigenous social organization; the concept of health for indigenous; characterization of environmental conflict and its health implications; health needs of the indigenous community and health promotion activities. The main findings of the study revolve around a concept of health that goes beyond the processes of illness, maintaining a close relationship with nature and the territory, which reverberates in different health needs, and some prioritized by public health policies. Thus, we consider important to rethink the "acting in health", and see the territoriality and intersectoral opportunities that contribute to the paradigm change. However, more than that, consider the holistic worldview of indigenous people who teach us the way to the concreteness of public health.